Are separate room test accommodations effective for college students with disabilities?. Issue 5 (3rd July 2020) - Weis, Robert; Beauchemin, Esther L.
Abstract: College students with attention-deficit/hyperactivity disorder (ADHD) and/or learning disabilities are frequently allowed to complete examinations in a separate, distraction-reduced setting. Although separate room test accommodations are believed to provide students with equal access to testing and thereby improve performance, little experimental research has examined their effects on actual test scores. We randomly assigned college students to complete a high-stakes Spanish language placement examination in either a group or separate room setting. Then, we categorized students based on their (1) disability status, (2) history of test accommodations, and (3) self-reported history of test anxiety. Results showed a significant setting x disability status interaction. Contrary to expectations, all students performed equally well in the group setting, but students with disabilities earned significantly lower scores than their classmates without disabilities when tested in a separate room. Similar results were found when we restricted our analyses to students with a history of test accommodations. Separate room testing had no effect on the scores of students with test anxiety. Altogether, our findings suggest that separate room testing does not mitigate the effects of ADHD, learning disabilities, and/or test anxiety on performance and, in some cases, may actually lower test scores.